(untitled) (Journal of Global Accounting, 2023)
The study ascertains the effect of intellectual capital on sustainability reporting of listed oil and gas firms in Nigeria Exchange (NGX) Group. The study specifically intends to determine the effect of Human Capital Efficiency, Structural Capital Efficiency and Capital Employed Efficiency on Environmental Sustainability Reporting, Economic Sustainability Reporting and Social Sustainability Reporting, respectively. Ex-post facto research design was applied. The population of this study comprises the entire twelve (12) Oil and Gas firms listed on the floor of the Nigerian Exchange (NGX) Group while the sample size comprises 11 of those firms. Secondary data were sourced from the annual reports of the selected firms over a period of fourteen (14) years spanning from 2008 to 2021. The results of the Panel Least Square (PLS) regression analysis conducted revealed that: Human Capital Efficiency has a significant and positive effect on Environmental Sustainability Reporting of listed Oil and Gas firms in Nigeria at 5% level of significance (β1=0.004298; p-value = 0.0181<0.05 ); Structural Capital Efficiency has a significant and positive effect on Economic Sustainability Reporting of listed Oil and Gas firms in Nigeria at 5% level of significance (β2=0.010781; p-value = 0.0000<0.05); Capital Employed Efficiency has a significant and positive effect on Social Sustainability Reporting of listed Oil and Gas firms in Nigeria at 5% level of significance (β3=0.262799; p-value = 0.0000<0.05). The study concludes that Intellectual Capital significantly affect Sustainability Reporting of listed Oil and Gas firms in Nigeria. It was recommended that corporate entities in Nigeria should invest in economic sustainability activities in all its ramification in order to boost their image/reputation thereby increasing their returns.